Bilanggo (Prison No. 10069) - Fernandez, Eddie; Romero, Chanda; Bautista, Beth
The real-life experiences behind bars of actor Eddie "Lagalag" Fernandez are depicted in this action-drama movie--https://www.imdb.com/title/tt0465918/?ref_=fn_al_tt_4